Examining Employee Buy-In for Organizational Change: A Structural Equation Model - Som Ratana; Chan Raksmey (Studies in Business and Economics, 2024)
Regardless of the prevalence of change, getting employees on board is hard to achieve. While the investigation of leadership and change readiness has been done continuously, the examination of staff involvement in change and working culture, particularly of the non-western world, has been less appreciated. This article addresses this gap by analysing the connection between employee buy-in, trust, relationship, and task-oriented culture. The main data was gathered from 214 respondents. They are employees at a higher education institution in Cambodia and have experienced a technology-driven change recently. The structural equation model reveals significant relationships between trust and working relationship as well as task-oriented culture, highlighting the pivotal role of these cultural attributes in fostering trust and facilitating buy-in for change. The findings contribute to Social Exchange Theory by showcasing the reciprocal exchange between the employee relationship and support in organizational changes and portray a missing trust among Cambodian employees. Recommendations were drawn from the findings for the betterment of change practices by the managers and practitioners.